Abnormal interhemispheric homotopic functional connectivity is correlated with gastrointestinal symptoms in patients with major depressive disorder. (December 2021) - Liu, Yi; Ou, Yangpan; Zhao, Jingping; Guo, Wenbin
Abstract: The severity of major depressive disorder (MDD) can be aggravated by gastrointestinal (GI) symptoms, but the neuroimaging mechanism underlying GI symptoms still remains unclear. In this study, we recruited 52 medication-free and first-episode MDD patients (35 with GI symptoms and 17 without GI symptoms) and 28 age-, sex-, and education-matched healthy controls to explore the inter-group differences in neuroimaging findings. All the participants underwent resting-state functional magnetic resonance imaging (fMRI) scan, and the functional connectivities that were reported to be abnormal in MDD were our focus of exploration. Voxel-mirrored homotopic connectivity (VMHC) method was used to explore the interhemispheric homotopic functional connectivity of all the subjects. Patients with MDD showed significantly different VMHC in brain regions in the default mode network (DMN), including the middle frontal gyrus, precuneus, inferior parietal lobule, and posterior cingulate cortex. Patients with GI symptoms exhibited significantly decreased interhemispheric homotopic functional connectivity in the middle frontal gyrus and superior frontal gyrus, compared with patients without GI symptoms. These results suggested that the DMN is involved in the neuropathology of MDD. Interhemispheric homotopic connectivity in specific regions could be applied as a biomarker to distinguish MDD patients with GI symptoms from those without GI symptoms.